To transform the function \( f(x) = 3^3 \) to the expression \( -f(3x - 2) + 1 \), we'll first calculate the value of \( f(3x - 2) \) and then apply the transformations step-by-step according to the order of operations.
Let's break down the transformations and fill in the table step-by-step.
Step 1: Evaluate \( f(x) = 3^3 \)
\[ f(x) = 27 \]
Step 2: Substitute \( 3x - 2 \) into \( f(x) \)
\[ f(3x - 2) = 3^{(3x - 2)} \]
Step 3: Rewrite the expression
Now we apply the positive exponent from \( f(3x - 2) \):
\[ f(3x - 2) = 3^{3x - 2} \]
Step 4: Apply the negative outside the function
Now we have to apply the negative sign:
\[ -f(3x - 2) = -3^{3x - 2} \]
Step 5: Finally add 1
\[ -f(3x - 2) + 1 = -3^{3x - 2} + 1 \]
Summary Table:
| Step | Expression | Calculation/Value | |------|------------|-------------------| | 1 | \( f(x) = 3^3 \) | \( 27 \) | | 2 | \( f(3x - 2) = 3^{3x - 2} \) | | | 3 | \( -f(3x - 2) = -3^{3x - 2} \) | | | 4 | \( -3^{3x - 2} + 1 \) | |
This table demonstrates the transition from \( f(x) = 3^3 \) to \( -f(3x - 2) + 1 \) by progressively rewriting the expressions while maintaining clarity on the order of operations applied. Each step involves applying one operation at a time until the complete transformation is achieved.